Playgroups for inclusion: Impacts of a playgroups intervention on child development, caregiving and connectedness goals using an experimental design - Barata, M. C.; Leitão, C.; Alexandre, J.; Russo, V.; Sousa, B. de. (European Journal of Psychology of Education, 2026)
Playgroups are gatherings for young children and their caregivers to engage in play-based and social activities. Evidence shows significant positive impacts for playgroup participants, including diverse families and families in socioeconomically disadvantaged circumstances. Still, weaknesses in the design of previous studies limit the validity of findings. This paper describes the impacts of a playgroups intervention between 2015–2017 targeting families with children up to 4 years old not participating in any of the available Early Childhood, Education and Care (ECEC) services in Portugal on standardized international measures of child development, home environment and caregiving practices, and socialization goals. Participants included 257 children (M age at pretest = 17.74 months, s.d. 11.51 months) and caregiver dyads in five districts. After a pretest assessment, all families were randomly assigned to one of two groups: an intervention group which included 10 months of playgroup intervention; and a control group who after the 10 month post-test assessment point, received 3 months of the playgroup intervention. Children in the intervention group scored significantly higher on average on a measure of developing ability to reason through manual and visuospatial problems. Caregivers in the intervention group were, on average, more likely to endorse their children's ability to maintain positive and harmonious relationships with others. Subgroup benefits on caregiver involvement were found for employed caregivers, and receptive and expressive language for diverse ethnic children. These results are aligned with intervention foci on the promotion of learning though play and positive relationships.